Pengaruh Penggunaan Media Pembelajaran Quizizz Terhadap Motivasi Belajar Siswa - Kartini, Sri; Putra, Hamda Kharisma; Mukti, Wandha Prayuda (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
This research was carried out at Veteran 1 Sukoharjo Vocational School with the aim of increasing the learning motivation of class X Broadcasting students through the use of Quizizz as a learning medium. The method applied was a descriptive quantitative approach involving 42 students as samples. Data collection was carried out using a Likert scale questionnaire. The main objective of this research is to evaluate the impact of using Quizizz on the level of student learning motivation in the class. It is hoped that the research results can provide a deeper understanding of the extent to which Quizizz can influence and increase student learning motivation in the context of class X Broadcasting learning at the vocational school. The use of Quizizz learning media significantly increases students’ learning motivation. As much as 46.6% of the variation in learning motivation can be explained by the use of Quizizz. The statistical test results show a significant effect with a calculated t value of 5.905 and a significance of 0.000. By increasing interest in the material, strengthening student understanding, and strengthening self-confidence, Quizizz plays a role in encouraging student learning motivation. The recommendation given is that teachers consider integrating Quizizz into classroom learning to support increased motivation and overall student learning outcomes.